A multi-colorimetric probe to discriminate between heavy metal cations and anions in DMSO–H2O with high selectivity for Cu2+ and CN−: study of logic functions and its application in real samples. Issue 47 (2nd September 2021) - Hamukwaya, Eunike; Naimhwaka, Johannes; Uahengo, Veikko
Abstract : A ditopic multi-colorimetric probe based on the phenylpridyl-thioic moiety (EN ) was synthesized via a Schiff base reaction mechanism and characterized using 1 H NMR and UV-vis spectroscopy. Abstract : A ditopic multi-colorimetric probe based on the phenylpridyl-thioic moiety (EN ) was synthesized via a Schiff base reaction mechanism and characterized using 1 H NMR and UV-vis spectroscopy. The colorimetric analyses carried out revealed that EN was capable of discriminating between a number of heavy metal cations via coordination induced charge transfer, as well as between anions through hydrogen bonding induced charge transfer, in DMSO–H2 O (9 : 1). In particular, the ditopic probe could spectrally and colorimetrically recognize the most toxic heavy metal cations of Cd 2+, Pb 2+ and Hg 2+, among others, in DMSO–H2 O. Additionally, EN was selective and sensitive to the presence of CN −, F −, AcO − and H2 PO4 − in the same solvent system as cations. The reversibility and reproducibility studies showed that EN exhibited complementary IMP/INH logic functions, based on colour and spectral switching (ON/OFF), modulated by F − /Al 3+ . The real time application of the probe was tested on food grade products to detect the presence of F − in toothpastes and mouthwash dissolved in water, as well as cations in underground water (normally saline), which displayed substantial responses. Thus, EN displayed an excellent scope of response and can thus be developed for real time sensing kits, which could be used instantly in on-field analysis. Theoretical studies were conducted to complement the experimental work.